Three-dimensional spatial transcriptomics uncovers cell type localizations in the human rheumatoid arthritis synovium - Vickovic, Sanja; Schapiro, Denis; Carlberg, Konstantin; Lötstedt, Britta; Larsson, Ludvig; Hildebrandt, Franziska; Korotkova, Marina; Hensvold, Aase H.; Catrina, Anca I.; Sorger, Peter K.; Malmström, Vivianne; Regev, Aviv; et al. (Communications biology, 2022)
The inflamed rheumatic joint is a highly heterogeneous and complex tissue with dynamic recruitment and expansion of multiple cell types that interact in multifaceted ways within a localized area. Rheumatoid arthritis synovium has primarily been studied either by immunostaining or by molecular profiling after tissue homogenization. Here, we use Spatial Transcriptomics, where tissue-resident RNA is spatially labeled in situ with barcodes in a transcriptome-wide fashion, to study local tissue interactions at the site of chronic synovial inflammation. We report comprehensive spatial RNA-Seq data coupled to cell type-specific localization patterns at and around organized structures of infiltrating leukocyte cells in the synovium. Combining morphological features and high-throughput spatially resolved transcriptomics may be able to provide higher statistical power and more insights into monitoring disease severity and treatment-specific responses in seropositive and seronegative rheumatoid arthritis.